Organizational structure, sense making activities and SMEs’ competitiveness - Valaei, Naser * (Emerald, 2017)
Purpose The purpose of this paper is to propose a model of competitiveness for small and medium-sized enterprises (SMEs) by investigating the structural relationship between organizational structure, knowledge quality (KQ) dimensions, improvisational creativity, compositional creativity and innovation in an emerging market – Malaysia – grounding in sense-making and organizational improvisational theories.